The role of nurses in the prevention of cervical cancer: Cervical screening, an unkept promise by the majority of women in Nigeria - Mary Opeyemi Adigun; Deborah Tolulope Esan; Benedict Tolulope Adeyanju; Babatunji Emmanuel Oyinloye (Journal of Integrative Nursing, 2023)
Cervical cancer remains a major public health problem accounting for continuous female death in developing countries. Cervical cancer is the second most common cancer in women globally with an estimated number of 500,000 new cases of cervical cancer and 273,000 mortalities annually. Cervical screening is the best cancer screening test in the history of medicine and most cost-effective of all medical screening tests. The study review aimed to highlight methods of cervical cancer prevention, identify the uptake of cervical screening among women, and explain the role of nurses in uptake of cervical screening. Cervical cancer is preventable and easily treatable if it is detected at early stages, but poor information on prevention and access to screening and treatment contributes to 90% of deaths. In the developing countries such as Nigeria, a large proportion of cervical cancers are diagnosed in advanced stages, with poor rates of survival. The three main methods for preventing cervical cancer are through primary prevention (human papillomavirus vaccination and health education), secondary prevention (cervical screening, early detection of precancerous lesions, and treatment), and tertiary prevention (measures to slow the progression or recurrence, surgical removal, radiotherapy, and chemotherapy). Nurses can help improve the acceptability of this neglected promise by focusing on health education on cervical screening and vaccination in prenatal clinics and infant welfare clinics where there are more women. Inclusion of cyberspace could also serve as a successful and popular platform for this health teaching. All nurses/midwives must preach and fervently work toward the WHO 90–70–90 plan for eradicating cervical cancer.